Analisis Pengaruh Rasio Aktivitas, Leverage Keuangan Terhadap Nilai Perusahaan Dengan Profitabilitas Ssebagai Variabel Intervening Pada Perusahaan Perkebunan Yang Terdaftar Di Bursa Efek Indonesia “BEI” (Periode 2015-2017) - Marli, Marli (Akutansi Bisnis & Manajemen ( ABM ), 2018)
This study aims to examine and analyze the effect of the proxied ratio of activities with Total Asset Turnover and Leverage proxied by the Debt to Equity Ratio on Corporate Values ​​proxied with Price to Book Value with Profitability proxied with Return On Assets as an intervening variable through Annual Financial Reports That Have Been Compiled By Plantation Subsector Companies listed on the Indonesia Stock Exchange. The Population In This Study Is Obtained By Using Purposive Sampling Methods In Plantation Companies Listed On The Indonesia Stock Exchange (IDX) During the 2015-2017 Period and based on the criteria that have been determined, a sample of 14 plantation companies is obtained. The analysis method used is Path Analysis, the development of multiple linear regression. By using multiple regression analysis, TATO has a significant positive effect on ROA. While DER has a significant negative effect on ROA. The TATO variable has a significant positive effect on PBV. DER variable has a significant negative effect on PBV and ROA has a significant positive effect on PBV. Based on path analysis and Sobel Test, it can be concluded that ROA mediates the effect of TATO on PBV. However, ROA does not mediate the effect of DER on ROA.